STORAGE OF EXTRA VIRGIN OLIVE OIL AND ITS IMPACT ON FATTY ACID LEVELS - Kráčmar, Stanislav; Fišera, Miroslav; Přikrylová, Veronika; Fišerová, Lenka; Málek, ZdenÄk; Tvrzník, Pavel (Journal of microbiology, biotechnology and food sciences, 2019)
Peroxide value, acid value, and fatty acid content were monitored during two-year storage in the following products: Luccese Olio extra vergine d´oliva (LOEVDO), Blanqueta extra-virgin olive oil (BEVOO) and Agrocreta extra-virgin olive oil (AEVOO). In LOEVDO and BEVOO, peroxide value increased by 50%; AEVOO showed 80% growth. Maximum acid value was found solely in LOEVDO (